2011
DOI: 10.4028/www.scientific.net/amr.188.90
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Grinding of SiC/Al Composites

Abstract: In this paper, grinding experiments on the machining of SiCp/Al composites using SiC grinding wheel have been carried out. The effect of the grinding parameters on the grinding forces, surface morphology and surface roughness were evaluated. The results indicate that the grinding depth has more significant effect on the grinding force than that of feed speed, and there are many fracture or crushed SiC particles on the ground surface. Therefore, the SiC wheels can be used for rough grinding of SiCp/Al composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The effect of the grinding parameters on the grinding force, as shown in Fig. 18, was investigated by Xu et al [188]. The results indicated that the grinding depth had a more significant effect on the grinding force than the feed speed; with increasing grinding depth and table feed speed, the grinding forces for both the tangential and normal components increased, and the increasing trend was more notable with a higher grinding depth.…”
Section: Surface Grindingmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the grinding parameters on the grinding force, as shown in Fig. 18, was investigated by Xu et al [188]. The results indicated that the grinding depth had a more significant effect on the grinding force than the feed speed; with increasing grinding depth and table feed speed, the grinding forces for both the tangential and normal components increased, and the increasing trend was more notable with a higher grinding depth.…”
Section: Surface Grindingmentioning
confidence: 99%
“…Zhang et al [187] compared the PCD compact (PDC) whisker with the CVD diamond whisker, and found that the PDC wheel had better edge evenness, which led to good machining quality. Xu et al [188] suggested the potential of using SiC wheels for rough grinding of SiC p /Al composites in consideration of their economic advantages. Zhong [189] reported that there was almost no subsurface damage except for rare cracked particles when fine grinding 10% (volume fraction) SiC p /Al composites with a diamond wheel.…”
Section: Surface Grindingmentioning
confidence: 99%
“…Because total material removal rate (MRR) was kept the same (5.08 mm 3 /s), the average MRR for one grain (MRR 1 ) was increased, leading to the increase in both F 1x and F 1z forces. 3,[42][43][44][45][46] With equations (3) and (4), the decrease rate of active abrasive-grain number might be larger than the increase rate of F 1x or F 1z forces, leading to the decrease in the cutting forces. 27,30,37 .…”
Section: Effects On Cutting Forcementioning
confidence: 99%
“…Comparing with the two-slot tool, the four-slot tool had less abrasive grains participating in machining, leading to higher tool wear and onegrain MRR 1 (the total MRR was the same, 3.81 mm 3 /s) and then resulting in higher F 1x and F 1z . 3,[43][44][45][46][47][48] Using equations (3) and (4), the increase rate of F 1x and F 1z might play a more important role than the decreasing rate of active abrasive-grain numbers, resulting in the cutting forces using the four-slot tool being higher than using the two-slot tool. 27,30,37 Effects of tool geometry.…”
Section: Effects On Cutting Forcementioning
confidence: 99%
See 1 more Smart Citation